1991
DOI: 10.1212/wnl.41.12.1874
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term benefit from prednisone therapy in Duchenne muscular dystrophy

Abstract: Two successive, 6-month, randomized, double-blind, controlled trials of prednisone showed that 0.75 mg/kg/d was the optimal dose to improve strength in boys with Duchenne muscular dystrophy (DMD). We attempted to maintain 93 boys on that dose for an additional 2 years. During the 3 years of observation, the decline in average muscle strength scores of all boys taking prednisone was 0.072 units/yr, as compared with an expected decline of 0.341 units/yr from natural history controls. The occurrence of side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0
7

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(136 citation statements)
references
References 0 publications
6
123
0
7
Order By: Relevance
“…Although the effects of CLA in humans remain controversial, two studies have found that CLA reduced body fat mass in overweight humans, 1,13 suggesting that it may be an adjunctive therapy for attenuating corticosteroid-induced fat gain in boys with DMD. 2,10 The ability of CLA, CrM, and ␣-LA to significantly reduce the retroperitoneal fat pad weight may ultimately prove helpful in attenuating body fat gains in DMD patients treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects of CLA in humans remain controversial, two studies have found that CLA reduced body fat mass in overweight humans, 1,13 suggesting that it may be an adjunctive therapy for attenuating corticosteroid-induced fat gain in boys with DMD. 2,10 The ability of CLA, CrM, and ␣-LA to significantly reduce the retroperitoneal fat pad weight may ultimately prove helpful in attenuating body fat gains in DMD patients treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…9,41 There are few therapeutic options available to boys with DMD; however, corticosteroid treatment has resulted in improved function and strength. 2,10,30 The exact mechanism by which corticosteroids exert their beneficial effect is unclear, but does not appear to involve a direct suppression of the inflammatory response. 16 Unfortunately, corticosteroids produce well-known and often serious side effects, 2,10,30 and alternative therapeutic strategies are therefore important.…”
mentioning
confidence: 99%
“…There are no curative therapies, but multiple independent clinical trials since 1974 [3] and meta-analyses firmly establish that chronic corticosteroids at a dose equivalent to 0.75/mg/kg/day of prednisone slow the progression of muscle weakness [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently the EK scale [20] was developed for non-ambulatory patients with Duchenne's muscular dystrophy (DMD) and SMA, the Wee Fim was utilized to quantify function in children with SMA in Hong Kong [11] and the functional research scale for ALS (FRS-ALS) scale was utilized in clinical trials with adult patients with ALS [21,22]. These scales are typically used as primary outcome measures for a treatment trial only when direct measure of power is not possible, though their use as a secondary measure is common [5,6,[23][24][25][26]. Though each of these tests were developed to assess functional skills in weak patients with neuromuscular disorders, construct of test items often precludes their use in assessing younger children.…”
Section: Introductionmentioning
confidence: 99%